2010
DOI: 10.1177/216507991005800303
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses' Perceptions of Health and Safety Related to Their Intention to Leave

Abstract: This study examined perceptions of general and emotional health among a statewide sample of nurses, and their assessment of employers' workplace health and safety initiatives. These variables and demographic data were then used to model predictors of intention to leave their work positions. A survey was mailed to all registered nurses in one state. Fifty-three percent responded ( n = 3,955). Findings suggested marked differences in perception of emotional health by age, with younger nurses reporting less posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Half of the nurses perceived their general health status as good. However, less nurses in the currents study, compared with Israeli female physicians, the general Israeli population, and registered nurses in Vermont, US (39.3% vs. 46.3%, 63.2% and 79%, respectively) perceived their health as very good or excellent (MOH, 2017; Val Palumbo et al, 2010; Wilf Miron et al, 2019). Results of respondents in the current study were comparable to those of Chinese and South Korean nurses, who rated their health perception as 2.58 and 2.82 on a 4‐points scales (fair or poor = 1, good‐2, very good = 3, excellent = 4) (Choi & Sung, 2013; Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Half of the nurses perceived their general health status as good. However, less nurses in the currents study, compared with Israeli female physicians, the general Israeli population, and registered nurses in Vermont, US (39.3% vs. 46.3%, 63.2% and 79%, respectively) perceived their health as very good or excellent (MOH, 2017; Val Palumbo et al, 2010; Wilf Miron et al, 2019). Results of respondents in the current study were comparable to those of Chinese and South Korean nurses, who rated their health perception as 2.58 and 2.82 on a 4‐points scales (fair or poor = 1, good‐2, very good = 3, excellent = 4) (Choi & Sung, 2013; Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, Hassan (2013) who studied the relationship among professional nurses' leadership style, organizational commitment and intention to leave and revealed that highly statistical significant deference in terms of the intent to leave between first line nurse managers and professional nurses. In addition to that, Palumbo, Rambur, McIntosh, & Naud, (2010) who studied registered nurses" perceptions of health and safety related to their intention to leave and illustrated that intention to leave is lower in those nurses who perceive better emotional health and more attention paid to safety and health initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…However, that means that the remaining 43.3% relate to other issues within the QOLS items or perhaps outside them. It is worth noting that there may be other confounding factors that may have an impact on the QOL of HCWs which may be unrelated to SSNIs, such as workplace discrimination or verbal abuse [49,50].…”
Section: Discussionmentioning
confidence: 99%